2010
DOI: 10.1016/j.jvs.2009.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Vascular complications of exposure for anterior lumbar interbody fusion

Abstract: Anterior exposure of the spine for ALIF can be performed safely with a team approach that includes a vascular surgeon. Preoperative evaluation by a vascular surgeon is advisable. Patients with increased BMI and bi-level exposures should be approached with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
98
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 24 publications
4
98
0
Order By: Relevance
“…Anterior lumbar interbody fusion (ALIF) gives better access to the disc space than posterior approaches, permitting more thorough discectomy and larger bone grafts [6,7]. However, ALIF is associated with urological and vascular complications [8]. Posterior procedures include posterior lumbar interbody fusion (PLIF) as well as transforaminal lumbar interbody fusion (TLIF).…”
Section: Introductionmentioning
confidence: 99%
“…Anterior lumbar interbody fusion (ALIF) gives better access to the disc space than posterior approaches, permitting more thorough discectomy and larger bone grafts [6,7]. However, ALIF is associated with urological and vascular complications [8]. Posterior procedures include posterior lumbar interbody fusion (PLIF) as well as transforaminal lumbar interbody fusion (TLIF).…”
Section: Introductionmentioning
confidence: 99%
“…Although in the early 1970s Stauffer and Coventry condemned this approach because, in their eyes, it meant "too much surgical trauma to the patient" (ref. 5 ), other authors have reported satisfactory results [6][7][8][9][10] . Even a laparoscopic approach for ALIF at the LS level has been described 11,12 , but it seems, this method was associated with considerable technical difficulties as well as with a higher complication rate because of the necessity for preparation and dissection of the major abdominal vessels 10,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Most venous injuries are related to the exposure rather than to implant placement. Mechanisms of injury include excessive venous traction, avulsion, and laceration 9,[14][15][16][17][18] . Peritoneal perforation during retroperitoneal exposure is not uncommon and in these cases immediate closure of these defects when recognized, was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular injuries are however, relatively rare complications ranging from 1.9 to 18% in the literature, with the highest rates being reported in the early 1990s [3][4][5][6][7][8][9][10]. General risk factors for an increased vascular injury risk are: current or previous osteomyelitis or discogenic infection, spondylolisthesis, osteophyte formation which is deemed to be an indicator for inflammatory reaction in the vessel-surrounding area, previous anterior surgery, transitional lumbo-sacral vertebra and cage migration.…”
Section: Case Presentationmentioning
confidence: 99%